1991
DOI: 10.1021/ac00002a009
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed amperometric detection of aliphatic alcohols in liquid chromatography

Abstract: The quantitative determination of aliphatic alcohols In liquid chromatography has been hindered by the lack of a sensitive detector. Aliphatic alcohols have no Inherent chromophore or fluorophore and are considered to be electrolnactlve under constant applied potential. The determination of underlvatized aliphatic alcohols by reversed-phase polymer-based chromatography with pulsed amperometric detection (PAD) Is direct, sensitive, and simple. PAD was applied to the determination of simple alcohols at Pt and Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
2
3

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 10 publications
(9 reference statements)
1
29
2
3
Order By: Relevance
“…Figure 4 shows the relevant results obtained in FIA at an applied potential of 0.5 V and using 0.1 mol L -1 NaOH plus different amounts of acetonitrile. In contrast with other common electrode materials, where attenuation of the sensitivity of the amperometric response was observed in mobile phases containing acetonitrile at millimolar levels [29,30], the anodic signals at the GC-Co electrode increased markedly with increasing acetonitrile concentration. In particular, a greatly enhanced amperometric response is observed for sucrose in comparison to that observed for fructose.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…Figure 4 shows the relevant results obtained in FIA at an applied potential of 0.5 V and using 0.1 mol L -1 NaOH plus different amounts of acetonitrile. In contrast with other common electrode materials, where attenuation of the sensitivity of the amperometric response was observed in mobile phases containing acetonitrile at millimolar levels [29,30], the anodic signals at the GC-Co electrode increased markedly with increasing acetonitrile concentration. In particular, a greatly enhanced amperometric response is observed for sucrose in comparison to that observed for fructose.…”
Section: Resultscontrasting
confidence: 69%
“…Figure 5 shows the results obtained in FIA at 0.5 V using 0.1 mol L -1 NaOH plus different amounts of methanol. In contrast with other transition metal electrodes where alcohols, and in particular methanol, are easy oxidized [13,30,31,32,33], the GC-Co electrode shows negligible electrocatalytic activity towards alcohol electrooxidation. In fact, as can be seen, the background current exhibited a percentage enhancement of about +10% upon addition of 5% methanol to the sodium hydroxide eluent (0.1 mol L -1 ).…”
Section: Resultsmentioning
confidence: 72%
“…Previous works have demonstrated that pulsed amperometry is able to solve such a drawback by the application of an additional potential pulse for cleaning the electrode surface from adsorbed oxidation products. 21,22 Thus, a sequence of two pulses was studied taking into consideration the detection of naproxen and the efficient electrode cleaning. This strategy resulted in highly repetitive current responses for naproxen injections.…”
Section: Resultsmentioning
confidence: 99%
“…20 Pulsed amperometry has also been applied to selective determinations of analytes at electrodes that undergo passivation due to adsorption of electrochemically generated oxidation products. 21,22 In the present study, it is reported an application of BIA with pulsed amperometric detection for fast determination of naproxen in pharmaceutical formulations. The application of two potential pulses provided naproxen detection by its electrochemical oxidation (at +1.5 V for 200 ms) without electrode contamination (+1.0 V for 100 ms for electrode cleaning) using an aqueous electrolyte.…”
Section: Introductionmentioning
confidence: 94%
“…However, a problem usually found when noble metals such as platinum and gold are used as substrate for anodic oxidation of glucose is related to the adsorption of reaction products, which blocks the electrode surface and hinders further oxidation [1]. A strategy that minimizes this problem involves a two-step electrochemical cleaning of the electrode surface by applying a series of potential steps at values where adsorbed material is conveniently removed [2,3]. Another very common approach for glucose sensing is based on the immobilization of an enzyme, usually glucose oxidase, on the electrode surface [4,5].…”
Section: Introductionmentioning
confidence: 99%